Biomass Accumulation, Photosynthetic Traits and Root Development of Cotton as Affected by Irrigation and Nitrogen-Fertilization - Chen, Zongkui; Tao, Xianping; Khan, Aziz; Tan, Daniel K. Y.; Luo, Honghai (Frontiers in Plant Science, 2018)
Limitations of soil water and nitrogen (N) are factors which cause a substantial reduction in cotton (Gossypium hirsutum L.) yield, especially in an arid environment. Suitable management decisions like irrigation method and nitrogen fertilization are the key yield improvement technologies in cotton production systems. Therefore, we hypothesized that optimal water-N supply can increase cotton plant biomass accumulation by maintaining leaf photosynthetic capacity and improving root growth. An outdoor polyvinyl chloride (PVC) tube study was conducted to investigate the effects of two water-N application depths i.e. 20 cm (H20) or 40 cm (H40) from soil surface and four water-N combinations [deficit irrigation (W55) and no N (N0) (W55N0), W55 and moderate N (N1) (W55N1), moderate irrigation (W75) and N0 (W75N0), W75N1] on the roots growth, leaf photosynthetic traits and dry mass accumulation of cotton crops. H20W55N1 combination increased total dry mass production by 29-82% and reproductive organs biomass by 47-101% compared with other counterparts. Root protective enzyme and nitrate reductase (NR) activity, potential quantum yield of photosystem (PS) II (Fv/Fm), PSII quantum yield in the light [Y(II)] and electron transport rate of PSII were significantly higher in H20W55N1 prior to 82 days after emergence. Root NR activity and protective enzyme were significantly correlated with chlorophyll, Fv/Fm, Y(II) and stomatal conductance. Hence, shallow irrigation (20 cm) with moderate irrigation and N-fertilization application could increase cotton root NR activity and protective enzyme leading to enhance light capture and photochemical energy conversion of PSII before the full flowering stage. This enhanced photoassimilate to reproductive organs.